Gerakan Sosial dan Nalar Islam Progresif: Mencari Titik Temu Kerangka Metateori - Ahmad Izudin (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2017)
This article will examine how progressive Islam’s reasoning can be a reference to free human beings from the exploitation and domination of social class? So what social movements can we do in the midst of crush the nation’s problems related to the exploitation of natural resources that increasingly vine? From this point on, I hope to get a meta-theory regulation that can be implied entirely for the benefit of society, in order to be free from exploitation and domination. To answer this important position, the discourse of social movements can be mapped into two, namely old social movement and new social movement. While Islam as a universal religion, there is no need to discuss theological-transcendental issues, but how the theology should create a new, more applicable avenue of dialectics to answer the question the rulers of powers domination. In the hope of a progressive, inclusive, open-minded, and pluralist theological doctrine. The results of this study may contribute to the development of science and the movement that became a turning point and reference in social change.Artikel ini hendak mengkaji bagaimana nalar Islam progresif yang dapat menjadi acuan untuk membebaskan manusia dari eksploitasi dan dominasi kelas sosial? Lantas gerakan sosial apa yang dapat kita lakukan di tengah himpitan persoalan bangsa terkait eksploitasi sumber daya alam yang kian menggurita? Dari titik ini, maka saya berharap mendapat satu regulasi metateori yang bisa diimplikasikan sepenuhnya untuk kepentingan masyarakat, agar bisa terbebas dari ekspolitasi dan dominasi. Untuk menjawab posisi penting ini, maka diskursus gerakan sosial dapat dipetakan menjadi dua, yakni old social movement dan new social movement. Sementara Islam sebagai agama universal, tidak perlu lagi membahas persoalan teologis-transendental, tetapi bagaimana teologi itu harus menciptakan ruang dealektika baru yang lebih aplikatif menjawab persoalan dominasi kekuasaan para penguasa. Dengan harapan munculnya doktrin teologis yang progresif, inklusif, open-minded, dan pluralis. Hasil kajian ini semoga memberikan kontribusi bagi perkembangan ilmu pengetahuan dan gerakan yang menjadi titik balik dan acuan dalam perubahan sosial.